Effectiveness of Soy Food for Stunting Prevention in Toddlers - Mukhlis, Mukhlis; Huriah, Titih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Stunting in toddlers is a global health problem with considerable consequences. One of the interventions to prevent stunting in toddlers is to provide local foods that are highly nutritious. Suitable foods are high in protein, saturated fat, essential amino acids, and high in vitamin B12. The journal review aimed to determine soy food's effectiveness in preventing stunting in toddlers. The method used is a systematic review by searching for articles in several media databases such as ProQuest, Ebsco and Scopus, which are used for sampling. Researchers filtered articles by setting exclusion criteria. The study on nutrition to prevent stunting, the 2017 to 2022 study, children or mothers with children aged 6-59 months and the inclusion criteria for the study protocol. In the next stage, the researcher assesses the journal's quality using a critical review from JBI; then, data extraction is carried out. The analysis study resulted in 182 articles, with the final results reviewing eleven papers that met the criteria. According to the survey, soy foods are given to toddlers and pregnant women to prevent stunting. In one study, researchers gave soybeans mixed with corn as additional food for toddlers. Supplementary feeding is carried out for six months to one year and can increase the growth and development of toddlers. A mixture of soy food with corn can also be used as an additional source of nutrition for toddlers. Abstrak: Stunting pada balita merupakan masalah kesehatan global dengan konsekuensi yang cukup besar. Salah satu intervensi untuk mencegah stunting pada balita adalah dengan memberikan makanan lokal yang bergizi tinggi. Makanan yang cocok adalah protein tinggi, lemak jenuh, asam amino esensial, dan vitamin B12 tinggi. Tujuan dari penelaahan jurnal untuk mengetahui efektivitas makanan kedelai dalam mencegah stunting pada balita. Metode yang digunakan yaitu Sebuah tinjauan sistematis dengan mencari artikel di beberapa media database seperti proquest, ebsco dan scopus yang digunakan untuk pengambilan sampel. Peneliti menyaring artikel dengan menetapkan kriteris eksklusi Kajian tentang gizi untuk mencegah stunting, kajian 2017 hingga 2022, anak atau ibu dengan anak usia 6-59 bulan dan kriteria inklusi kajian protokol. Pada tahap selanjutnya peneliti menilai kualitas jurnal menggunakan critical review dari JBI, kemudian dilakukan ekstraksi data. dari hasil Studi analisis menghasilkan 182 artikel dengan hasil akhir mengulas sebelas makalah yang memenuhi kriteria. Menurut survei, makanan kedelai diberikan kepada balita dan ibu hamil untuk mencegah stunting. Dalam sebuah penelitian, peneliti memberikan kedelai yang dicampur dengan jagung sebagai makanan tambahan untuk balita. Pemberian makanan tambahan dilakukan selama enam bulan hingga satu tahun dan dapat meningkatkan pertumbuhan dan perkembangan balita. Campuran makanan kedelai dengan jagung juga daapat dijadikan sebagai sumber nutrisi tambahan untuk balita.